2013
DOI: 10.1016/j.atherosclerosis.2013.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD31+ leukocyte frequency is associated with cardiovascular risk factors

Abstract: Objectives CD31 identifies a heterogeneous population of cells in the blood, consisting of mature leukocytes and platelets, as well as smaller numbers of endothelial and progenitor cells. Because unfractionated CD31+ blood cells have demonstrated angiogenic properties in vivo, we hypothesized that circulating CD31+ cells would be related to the presence of cardiovascular risk factors in humans. Methods and Results We studied 1,487 participants, free of cardiovascular disease, from the Framingham Offspring St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
4
7
0
Order By: Relevance
“…Moreover, we have detected CD31 in other cell types likewise, especially in cancer‐derived leukocytes it was identified quite abundantly as well (data not shown). CD31 + leukocytes have also been observed by others, for example, in patients with cardiovascular diseases . The finally obtained signature correctly classified endothelial cells isolated from the liver, bone marrow, lung, and ovaries, all at normal and inflammatory activated cell states (data not shown).…”
Section: Resultssupporting
confidence: 57%
“…Moreover, we have detected CD31 in other cell types likewise, especially in cancer‐derived leukocytes it was identified quite abundantly as well (data not shown). CD31 + leukocytes have also been observed by others, for example, in patients with cardiovascular diseases . The finally obtained signature correctly classified endothelial cells isolated from the liver, bone marrow, lung, and ovaries, all at normal and inflammatory activated cell states (data not shown).…”
Section: Resultssupporting
confidence: 57%
“…We found that smoking was associated with a decrease in BM CD45 + CD31 + lymphocytes. Similar to our findings, Ge et al [14] found a negative association between smoking and the level of circulating CD45 +− CD31 dim lymphocytes in healthy men and women. Further investigation of this cell type is warranted to determine its role in the prevention or repair of cardiac injury.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, increased age was inversely associated with the frequency of CD45 + CD31 + lymphocytes. This is similar to the findings of, both Hur et al [19] and Ge et al [14] who showed an inverse correlation between the level of circulating peripheral blood CD31 + T cells and age. One possible explanation for this decrease in cell number with age is age-related apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We focused our study on CD31 − DP-MSCs to exclude cells that may express some of these markers although being not MSCs. Indeed, some endothelial cells are known to express CD146 and Stro-1, and natural killer cells and some lymphocytes may express CD56 (Shi and Gronthos, 2003; Woodfin et al, 2007; Crisan et al, 2008; Ge et al, 2013; Lv et al, 2014; Harkness et al, 2016; Melsen et al, 2016). Flow cytometry was recently used to characterize the various populations of immune cells present in the human DP with a strategy of progressive cell gating (Gaudin et al, 2015), and we designed in the present study a similar strategy to allow for the identification and quantification of DP-MSC subpopulations.…”
Section: Discussionmentioning
confidence: 99%